Development of MOF-Coated Electrostatic Mems Resonators for Gas and Chemical Sensing Applications - Hemid, Mohamed Mahmoud (2024)
A Master of Science thesis in Mechatronics Engineering by Mohamed Mahmoud Hemid entitled, “Development of MOF-Coated Electrostatic Mems Resonators for Gas and Chemical Sensing Applications”, submitted in April 2024. Thesis advisor is Dr. Mehdi Ghommem and thesis co-advisor is Dr. Rana Sabouni. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).